'Mapping the Most Influential Art Districts in Shanghai (1912-1948) through Clustering Analysis'. Issue 6 (7th November 2022) - Zheng, Jane; He, Jie; Fan, Zhen; Zhang, Sabrina P.Y.; Lin, Hui; Leung, Yuen Sang
Abstract: This research proposes a new method to map and classify art clusters, combining multiple dimensions of spatial and social network analyses. This method innovatively blends a historic GIS approach, spatial statistics and qualitative data analysis, and experiments with the Republican-period of Shanghai art world, known as the golden age of art and culture in Shanghai. The outcome is the identification of 11 major art clusters in eight selected years with unique characteristics. It also uncovers a partially correlated yet dialectic relationship between social network dynamics and cluster transformation in Shanghai. These findings fill a knowledge gap in Chinese art history.